(untitled) (Diyala Journal of Engineering Sciences, 2014)
ﯿﻬدف ﻫذا اﻟﺒﺤث اﻟﻰ دراﺴﺔ ﺘﺎﺜﯿر اﻀﺎﻓﺔ اوﻛﺴﯿد اﻟﺤدﯿد واوﻛﺴﯿد اﻻﻟﻤﻨﯿوم ﻋﻠﻰ اﻟﺨواص اﻟﻤﯿﻛﺎﻨﯿﻛﯿﺔ ﻟﻠﺒوﻟﻲ اﺜﯿﻠﯿن، ﺤﯿث اﺴﺘﺨدﻤت ﻨﺴب وزﻨﯿﺔ ﻤﺨﺘﻠﻔﺔ ﻤن اﻻﻛﺎﺴﯿد وﻫﻲ)١٠,%٧,%٥,%٣,%١%(. ﻟﺘﻘﯿﯿم ﻤدى ﺘﺎﺜﯿر اﻻﻛﺎﺴﯿد اﻟﻤظﺎﻓﺔ ﻋﻠﻰ اﻟﺨواص اﻟﻤﯿﻛﺎﻨﯿﻛﯿﺔ ﺘم اﺠراء اﺨﺘﺒﺎر اﻻﻨﻀﻐﺎط وﺘﺤدﯿد اﺠﻬﺎد اﻻﻨﻀﻐﺎط اﻻﻗﺼﻰ وﻤن ﺜم ﻗﯿﺎس ﻨﻘطﺔ اﻟﻠﯿوﻨﺔ. وﻤن ﺨﻼل اﻟﻨﺘﺎﺌﺞ اﻟﺘﻲ ﺘم اﻟﺘوﺼل اﻟﯿﻬﺎ ﺘﺒﯿن ان اﻓﻀل ﻤﻘﺎوﻤﺔ اﻨﻀﻐﺎط ﻛﺎﻨت ﻋﻨد اﻀﺎﻓﺔ اوﻛﺴﯿد اﻟﺤدﯿد ﺒﻨﺴﺒﺔ ٧٪ ، اﻤﺎ ﺒﺎﻟﻨﺴﺒﺔ ﻻوﻛﺴﯿد اﻻﻟﻤﻨﯿوم ﻓﻛﺎﻨت اﻓﻀل ﻗﯿﻤﺔ ﻤﻘﺎوﻤﺔ اﻨﻀﻐﺎط ﻋﻨد اﻀﺎﻓﺔ ٥٪. ﻛذﻟك ﺘﺒﯿن ان اﻟﻌﻼﻗﺔ ﻛﺎﻨت طردﯿﺔ ﻤﺎﺒﯿن زﯿﺎدة اﻟﻨﺴب اﻟﻤﻀﺎﻓﺔ وﻨﻘطﺔ اﻟﻠﯿوﻨﺔ. وﻗد ﻟوﺤظ ان اﻀﺎﻓﺔ اوﻛﺴﯿد اﻟﺤدﯿد واوﻛﺴﯿد اﻻﻟﻤﻨﯿوم ﻟﻐﺎﯿﺔ ١٠% ادت اﻟﻰ اﻨﺨﻔﺎض ﻓﻲ ﻗﺎﺒﻠﯿﺔ اﻟﺘﺸﻛﯿل اﺜﻨﺎء اﻻﻨﻀﻐﺎط This research aims to study the effect of adding Iron Oxide Fe2O3 and Aluminum Oxide Al2O3 on mechanical properties of Low Density Polyethylene (LDPE), where various weight percentages of the oxides of (1%, 3%, 5%, 7%, and 10%) were used.To investigate the effect of adding oxides on the mechanical properties of (LDPE), Compression test was performed and the ultimate compression test was determined, then the softening point was measured. From the results reached it was concluded that the best compression strength was recorded at 7% addition of Iron Oxide, while for the Aluminum Oxide the highest compression strength was recorded at 5%. Also it was found that the relationship was directly proportional between softening point and oxide percentage. It was noticed that the adding of the oxides up to 10% results in decreasing of the formability during compression.